1976
DOI: 10.1289/ehp.7615131
|View full text |Cite
|
Sign up to set email alerts
|

Determination of human body burden baseline date of platinum through autopsy tissue analysis.

Abstract: Results of analysis for platinum in 97 autopsy sets are presented. Analysis was performed by a specially developed emission spectrochemical method. Almost half of the individuals studied were found to have detectable platinum in one or more tissue samples. Platinum was found to be deposited in 13 of 21 tissue types investigated. Surprisingly high values were observed in subcutaneous fat, previously not considered to be a target site for platinum deposition. These data will serve as a human tissue platinum burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Following the exposure of rats to Pt compounds via inhalation, the highest concentrations of Pt were found in the lungs and the kidneys 30. The analysis of the Pt content of non-occupationally exposed human autopsied tissue found the highest concentrations in the subcutaneous fat, the kidneys, the pancreas and the liver 31. In vitro permeation studies reported that most of the Pt was retained inside the skin, leading the authors to state that a Pt reservoir may form inside the skin from where Pt could be gradually released.…”
Section: Discussionmentioning
confidence: 99%
“…Following the exposure of rats to Pt compounds via inhalation, the highest concentrations of Pt were found in the lungs and the kidneys 30. The analysis of the Pt content of non-occupationally exposed human autopsied tissue found the highest concentrations in the subcutaneous fat, the kidneys, the pancreas and the liver 31. In vitro permeation studies reported that most of the Pt was retained inside the skin, leading the authors to state that a Pt reservoir may form inside the skin from where Pt could be gradually released.…”
Section: Discussionmentioning
confidence: 99%